THE PRAGMATIC RELATIONSHIP OF ELEMENTS IN THE APPLIED ELEMENTS EXPRESSED IN A LITERARY TEXT - Bektemirov Zokhid Nodirovich (The Conference Hub, 2025)
Linguistics, the study of language, offers diverse branches that explore how language functions in different contexts. Among these, pragmatics plays a crucial role in understanding the meaning of words beyond their literal interpretation, focusing on how speakers use language in real-world situations to achieve specific communicative goals. Pragmatics deals with context, intent, and the social aspects of communication, providing insight into how meaning is shaped by factors such as the speaker's intentions, the listener's interpretation, the surrounding circumstances, and cultural norms. In literary texts, the pragmatic relationship of language elements becomes even more significant. Authors employ various linguistic tools to evoke specific meanings, convey emotions, and create an engaging narrative. These tools, often referred to as "applied elements" (adjectives, adverbs, discourse markers, etc.), are crucial for constructing the narrative’s atmosphere, revealing character traits, and guiding the reader through the story. The way these elements function in literary works is not only about modifying nouns or verbs but also about shaping how the reader perceives the social dynamics, emotions, and deeper layers of meaning embedded in the text.